MANAJEMEN PENDIDIKAN ISLAM BERBASIS GLOKALISASI PADA LEMBAGA PENDIDIKAN ISLAM: STUDI KASUS PADA YAYASAN GENERASI MADANI BANTEN - Kasronudin; Fahmi Hauzan Rafif; Iskandar Balad; Ahmad Suryadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the model of Islamic education management based on glocalization in contemporary Islamic educational institutions, with a case study at the Generasi Madani Banten Foundation, which manages three educational units: TKIT Generasi Madani, SDIT Peradaban Mulia, and SMP Islam Al-Bashri Boarding School. The phenomenon of globalization brings a dual challenge: westernization, which tends to be secularistic, and the urgency of indigenization, which seeks to strengthen local identity. This research employs a qualitative approach with a descriptive-analytical case study method. Data were collected through in-depth interviews, observation, and documentation study, then analyzed using data condensation, data display, and conclusion drawing. The results indicate that the Generasi Madani Banten Foundation systematically integrates three main dimensions: the global dimension (digitalization, 21st-century competencies, foreign languages), the local dimension (Banten's cultural wisdom and community empowerment), and the Islamic dimension (aqidah, worship, morals, and Quranic memorization/tahfiz). This integration is manifested through comprehensive management functions, ranging from strategic planning, trust-based (amanah) organizing, integrated curriculum implementation, to holistic quality evaluation. This study concludes that glocalization-based management successfully positions Islamic educational institutions as competitive global agents of modernization while firmly maintaining their Islamic character and local cultural roots.